Variability, Heritability and Genetic Advance for Yield and Yield Contributing Characters in Tomato (Lycopersicon esculentum Mill.) - Khanom, MSR; Khan, MHK; Hassan, L (Progressive Agriculture, 2013)
The experiment was conducted during rabi season, 2003-2004 at the Field Laboratory of the Department of Genetics and Plant Breeding, Bangladesh Agricultural University, Mymensingh. Genotypic variability, heritability and genetic advance for yield and yield contributing characters were studied on 55 tomato genotypes. Data were recorded on number of primary branches per plant, days to first flowering, plant height, number of bunches per plant, number of fruits per plant, individual fruit weight, number of seeds per fruit, dry matter content of fruits, pH level of fruit juice and yield per plant. Very little differences were observed between genotypic coefficient of variation and phenotypic coefficient of variation for all the characters except dry matter content and yield per plant indicating that they were less influenced to environmental factors for their phenotypic expression. High heritability estimates coupled with high genetic advance in percentage of mean were obtained for number of primary branches per plant, number of days to first flowering, plant height, number of bunches per plant, number of fruits per plant, individual fruit weight and number of seeds per fruit indicating wide scope for improvement through selection of these traits. DOI: http://dx.doi.org/10.3329/pa.v19i1.16982 Progress. Agric. 19(1): 1 - 5, 2008